Impatiens uncata (Balsaminaceae), a new species from Hunan, China - Qiu, Kan-Ying; Zhou, Jian-Jun; Xiang, Jian-Feng; Liu, Ang; Fei, Dong-Bo; Liu, Song; Yu, Xun-Lin; Cong, Yi-Yan (Phytotaxa, 2024)
Impatiens uncata, a new species from Ningyuan County, Hunan, is described and illustrated. The new species is superficially similar to I. huangyanensis in having racemose and 2-flowered (rarely many-flowered) inflorescences, fusiform capsule and ellipsoid seed, but is distinguishable from the latter by its obviously taller height, leaves with ovate or ovate-lanceolate blades and longer petioles, purple flowers, longer bracts, broadly ovate-rounded lateral sepals, white broadly funnelform lower sepal, 2-lobed spur with a swollen apex, purplish dorsal petal, white basal lobes, and bigger distal lobes with a retuse apex.